Mediação para a gestão social - o caso do colegiado de desenvolvimento territorial do centro serra do Rio Grande do Sul - Facco, Hector dos Santos (2021)
The Brazilian territorial policy has an important milestone in 2003, with the creation of the Secretariat for Territorial Development (SDT) by the Ministry of Agrarian Development (MDA). Following this, a set of actions was implemented that unfolded in several moments, such as the National Program for Sustainable Development of Rural Territories - PRONAT (2005), the Citizenship Territories Program (2008) and, in its latest form, the Public Call No. 11/2014 for the implementation and maintenance of Extension Centers in Territorial Development (NEDET's), aimed at advising the Territorial Development Councils (CODETER's) in each rural territory of the country. This Public Call was established through an institutional partnership between SDT-MDA, the National Council for Scientific and Technological Development (CNPq) and the Special Secretariat of Policies for Women of the Presidency of the Republic (SPM-PR). One of the main lines of action of NEDET's with the CODETER's was to qualify and expand the process of social management in the territories. Thus, this work aims to evaluate and reflect on the social mediation exercised by NEDET Centro Serra with the CODETER Centro Serra of Rio Grande do Sul, with a view to promoting the social management process. Methodologically, a qualitative approach was used, with the triangulation of different research instruments, such as the use of bibliographic and documental sources, diagnostic tools (sociograms), questionnaires of the Social Management Index - IGS (SDT-MDA); and the realization of semi-structured interviews with the mediators linked to NEDET Centro Serra. As results, the expansion of social participation in the CODETER Centro Serra, especially of the priority publics of the territorial policy (women, young people, settlers in agrarian reform projects, traditional communities and indigenous peoples); the difficulty with the participation of the local public power actors; the importance of building criteria and agreements for decision-making articulated to the Territorial Plan for Sustainable Rural Development (PTDRS) of the Centro Serra territory; and, finally, the importance of qualified mediation by an advisory body (NEDET's) dedicated to overcoming the problems related to the process of social management conducted by collegiate instances, such as the CODETER's in the case of Brazilian territorial policy.